Effects of small-sided game training on lower limb explosive strength in handball players: a single-arm meta-analysis - Wang, Ran; Li, Quanzhi; Xue, Weiqi (Frontiers in Sports and Active Living, 2024)
Objective: This meta-analysis systematically evaluates the influence of small-sided game (SSG) on the counter-movement jump (CMJ) height and 20-meter sprint capabilities of handball players. Methods: Systematic searches of PubMed, Web of Science, Cochrane Library, and China National Knowledge Infrastructure(CNKI) databases were performed up to February 2024. Results: A total of 8 studies with 184 participants were included. Meta-analysis demonstrated significant improvements in CMJ (cm) in handball players (Weighted Mean Difference (WMD)=-1.06, 95% CI[-1.99, -0.12], Z=2.22, P=0.03). For the 20m sprint capability, the results were WMD=-0.07, 95% CI[-0.14, 0.01], Z=1.82, P=0.07. Subgroup analysis by age: ≥19 years old WMD=-0.02, 95% CI[-0.08, 0.03], and <19 years old WMD=-0.10, 95% CI[-0.21, 0.00], indicating no significant impact on the 20-m (s) performance improvement. Gender subgroup analysis showed male WMD=-0.01, 95% CI[-0.08,0.07] and female WMD=-0.11, 95%CI[-0.19, -0.03; P<0.05], suggesting better improvement in females. Conclusion: The present study reveals that SSG training has varying impacts on 20m sprint performance among handball players of different ages and genders. Specifically, there is no significant improvement in the 20m sprint performance between players aged <19 and ≥19, while female players show greater improvement in the 20-m (s) compared to male players. These differences could be attributed to the physiological, psychological, and adaptive training differences between athletes of different ages and genders. Although SSG plays an essential role in training handball players, particularly in enhancing lower limb explosive strength and overall game performance, it is recommended to combine SSG with other targeted strength and explosive power training to maximize the enhancement of lower limb explosive power in handball players.Comprehensive training can effectively improve the lower limb explosive strength of athletes while also addressing the development of other key athletic qualities to achieve the best training outcomes. Therefore, coaches should fully consider the individual differences and training needs of athletes when designing training plans, and reasonably allocate the proportion and sequence of SSG with other training methods to maximize training effectiveness.